Full and constrained Pareto optimality with incomplete financial markets - Concetta Mendolicchio; Tito Pietra (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2018)
We study the efficiency properties of equilibria in a neighborhood of economies with Pareto optimal (PO) initial endowments, when the number of agents is finitely large. We provide conditions under which, for all the economies in some open neighborhood of the PO reference economy, all the equilibria are constrained PO (CPO). We also provide conditions under which each open neighborhood of these exceptional PO economies contains both open sets of economies with CPO equilibria and open sets of economies where CPO fails. – – Wir untersuchen die Effizienzeigenschaften von Gleichgewichten in einer ökonomischen Umgebung mit Pareto-optimale (PO) Anfangsausstattungen, wenn die Anzahl der Agenten endlich groß ist. Wir zeigen Bedingungen, unter denen für alle Volkswirtschaften in einer offenen Umgebung der PO-Referenzökonomie, alle Gleichgewichte beschränkte PO (CPO) sind. Wir zeigen auch Bedingungen, unter denen jede offene Umgebung dieser außergewöhnlichen PO-Ökonomien sowohl offene Mengen von Ökonomien mit CPO-Gleichgewichten enthält als auch offene Mengen von Ökonomien, in denen CPO versagt.
Keywords: D51; D52; 330; GEI; constrained Pareto inefficiency; numeraire assets